2022
DOI: 10.1002/aenm.202270136
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Strategy for Highly Efficient and Super Flexible Thick‐film Organic Solar Cells (Adv. Energy Mater. 31/2022)

Abstract: Organic Photovoltaics In article number 2201614, Shuguang Wen, Chunming Yang, Xichang Bao, and co‐workers report a synergistic strategy to fabricate efficient and super flexible thick‐film organic solar cells (OSCs). The proposed comprehensive regulation of intra‐ and inter‐domain interactions in the active layer points to an important research direction for the thickness sensitivity and mechanical stability issues facing flexible OSC applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Then crack‐onset‐strain (COS) as another important figure‐of‐merit for all‐polymer blend is evaluated, which represents the film ductility. [ 42–47 ] As presented in Figure 1d and Table S1 (Supporting Information), the strain‐stress curves of all‐polymer blends are presented in Figure d and their derived COS and mechanical toughness values are listed in Table S1 (Supporting Information). It was found that the proper addition of PTQ10 could significantly boost the ductility of active layers in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Then crack‐onset‐strain (COS) as another important figure‐of‐merit for all‐polymer blend is evaluated, which represents the film ductility. [ 42–47 ] As presented in Figure 1d and Table S1 (Supporting Information), the strain‐stress curves of all‐polymer blends are presented in Figure d and their derived COS and mechanical toughness values are listed in Table S1 (Supporting Information). It was found that the proper addition of PTQ10 could significantly boost the ductility of active layers in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, numerous published results indicate the high flexible properties of fullerene free PM6:Y12 BHJ semiconducting polymers. [ 91–94 ] Therefore, in order to better understand if the mechanical tests are explaining OPD's degradation, we fabricated and tested a new OPD under similar processing and operating conditions (i.e., biased at −1.7 V and 10 mW cm −2 white light illumination) and have recorded the J d and the J ph values every 15 min under non‐bending conditions in ambient air. The J d and J ph values recorded for the first measurement were 1.18 and 186 µA cm −2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The thick active layer also weakens the strength of internal electric field, which is apparently unfavorable to the photocharge collection. [9,10] Together with the longer charge transport distance to electrode and the imbalanced charge mobility, the thick active layer device demonstrates more severe charge recombination than the 100 nm active layer device. [9,11] To overcome the limitations of reduced photocharge generation and collection in thick BHJ film OSCs, it is rational to put forward a strategy that can simultaneously optimize the exciton splitting efficiency and the internal electric field.…”
Section: Introductionmentioning
confidence: 99%